Utilization of Coconut Plantation Weeds as a Sustainable Feedstock for Biochar Production - Dissanayaka Nuwandhya S.; Sandakelum Tharaka; Nuwarapaksha Tharindu D.; Udumann Shashi S.; Nugara Ruwani N.; Atapattu Anjana J. (Contemporary Agriculture)
Biochar, a carbon-rich and highly porous material, is created through the process of pyrolysis, a thermal decomposition of raw materials conducted in a controlled, low or no oxygen environment. Our research aimed to investigate the feasibility of utilizing coconut plantation weeds as a potential source for biochar production. The study encompassed two essential phases: a laboratory experiment conducted at the Agronomy Division of the Coconut Research Institute and a field experiment at the Rathmalagara Research Center, affiliated with the same institute. In the laboratory experiment, biochar was produced from six distinct types of coconut plantation weeds, including Megathyrsus maximus, Imperata cylindrica, Lantana camara, Chromoleana odorata, Stachytarpheta jamaicensis, and Urena lobata. The biochar was produced at a temperature of 500°C, with a residence time of 30 minutes. The resulting biochar samples underwent comprehensive analysis to evaluate various characteristics, such as conversion efficiency, pH, electrical conductivity (EC), moisture content, volatile matter content, ash content, and fixed carbon content. The biochar derived from Megathyrsus maximus demonstrated the highest conversion efficiency of 32.76% and displayed high-quality characteristics. In the field experiment, biochar was produced using a double-chamber pyrolyzer and employed three different stocking densities, with Megathyrsus maximus as the primary feedstock. The outcomes revealed that the biochar generated at a high stocking density of 72.10 kgm-3 yielded a remarkable conversion efficiency of 32% and exhibited high-quality biochar. Based on the experimental findings, Megathyrsus maximus demonstrates strong potential as an ideal feedstock for biochar production at the field level using a double-chamber pyrolyzer. These results emphasize the potential for sustainable biochar production from readily available, renewable resources, such as weed biomass from coconut plantations, further highlighting the environmental and agricultural benefits of this approach.